Utilizing Hollow-Structured Bamboo as Natural Sound Absorber - PUTRA, Azma; Abd KHAIR, Fazlin Binti; Mohd NOR, Mohd Jailani (Archives of Acoustics, 2015)
Studies to find alternative low environmental-impact materials for acoustic absorbers are still progressing, particularly those originated from natural materials. However, most of the established works are mainly focused on the fibrous-type absorbers. Discussion on the non-fibrous-type absorbers is still lacking and this therefore becomes the objective of this paper. Use of bamboo by utilizing its hollow structure to absorb sound energy is discussed here. The normal incidence absorption coefficient was measured based on the length and diameter of the bamboo, as well as different arrangement of the bamboo structure subjected to the incidence sound, namely, axial, transverse, and crossed-transverse arrangements. The trend of absorption coefficient appears in peaks and dips at equally spacing frequencies. For all arrangements the peak of absorption can reach above 0.8. Introducing an air gap behind the bamboo shifts the peak absorption to lower frequency. Covering the front surface of the absorber improves the sound absorption coefficient for axial arrangement by widening the frequency range of absorption also towards lower frequency range. The transverse arrangement is found to have average absorption coefficient peaks of 0.7 above 1.5 kHz. By arranging the bamboo structure with crossed-transverse arrangement, the suppressed absorption peaks in normal transverse arrangement can be recovered.